Risk Level of Exercise Posture on Musculoskeletal Disorder in Petanque Athletes - Arimbi; Andi Ainun Zulkiah Surur; Ulfah Widyastuti Arsal; Andi Sri Dewi Anggraeni (Universitas Negeri Semarang, 2025)
This study aims to analyse the risk level of exercise posture on musculoskeletal disorders (MSDs) at the Faculty of Sports and Health Science , Makassar State University (UNM). Petanque requires athletes to perform repetitive movements and maintain certain body positions, especially when throwing, which can potentially cause musculoskeletal disorders. This study employs a descriptive observational design with a cross-sectional approach. Data were obtained through direct observation of athletes' working posture during activities and analysed using the Rapid Upper Limb Assessment (RULA) method to assess the level of posture risk for musculoskeletal complaints. The results of the analysis showed that most athletes were in the low to moderate risk category, especially in the back, upper arm and wrist, caused by non-ergonomic body positions when throwing. Based on these results, it can be concluded that the posture of petanque athletes contributes to an increased risk of musculoskeletal disorders, thus requiring attention to the application of ergonomic principles and improvement of posture techniques in training to reduce the potential for musculoskeletal injuries.